Silence of TANK-binding kinase 1 (TBK1) regulates extracellular matrix degradation of chondrocyte in osteoarthritis by janus kinase (JAK)-signal transducer of activators of transcription (STAT) signaling. Issue 1 (1st January 2022) - Sun, Peng; Xue, Yuan
ABSTRACT: TANK-binding kinase 1 (TBK1) was previously reported to be critical for the regulation of osteoclast differentiation. However, its function in osteoarthritis (OA) has not yet been determined. This study aims to reveal the role of TBK1 in the extracellular matrix (ECM) degradation in OA. C57BL/6 J mice were subjected to anterior cruciate ligament transection (ACLT) surgery to establish an OA animal model. ATDC5 cells were treated with IL-1β to construct a cell model of OA. Changes in the expression of TBK1 were analyzed by qRT-PCR, Western blotting, and immunohistochemistry. Safranin O-fast green staining, ELISA, and Western blotting were performed to evaluate the ECM degradation. By searching GSE75181 and GSE6119 datasets, TBK1 was found to be highly expressed in the OA model. Its upregulation was also confirmed in ACLT mice and in a cell model of OA. Silencing of TBK1 reduced cartilage degradation, OARSI score, and serum levels of CTX-II and COMP. Silencing of TBK1 attenuated ECM degradation, as ADAMTS-4, MMP3, and MMP13 were downregulated, whilst SOX9, collagen II, and aggrecan were upregulated. Furthermore, TBK1 activates the JAK/STAT signaling pathway. Transfection of cells with the STAT3 overexpression plasmid blocked the beneficial effects of TBK1 silencing. In conclusion, TBK1 is highly expressed in OA. Silencing of TBK1 inhibited ECM degradation.